Clinical Profile and Sensitivity Pattern of Salmonella Serotypes in Children: A Hospital Based Study - Joshi, BG; Keyal, K; Pandey, R; Shrestha, BM (Journal of Nepal Paediatric Society, 2011)
Introduction: Enteric fever is a systemic infection caused by the bacteria, Salmonella enterica serovar Typhi (S.typhi) and Salmonella enterica serovara Paratyphi (S. paratyphi A, B and C). Most of the burden of the disease is limited to the developing world and the disease still has the issues like wide spectrum of clinical presentation and multidrug resistance. Objectives: This study was done to analyze the clinical profile and antibiotic sensitivity pattern in the cases of culture positive enteric fever. Methods: A prospective cross-sectional study was conducted in Civil Service Hospital from February 2010 to January 2011 in the paediatric population in the age group of 2 to 14 years. Children with Salmonella species isolated in blood culture were included in the study. Results: Out of the 40 children with culture positive enteric fever, male to female ratio was 1.3:1 with common age group between 11-14 years. S typhi was isolated in 25 cases while S. paratyphi in 15 cases. Clinical features of S. typhi and S. paratyphi were indistinguishable. Both S.typhi and S. paratyphi were found to be 100% sensitive to drugs like Ceftriaxone, Cefotaxime, Cefixime and Chloramphenicol. Sensitivity to Ofloxacin was 100% in S. paratyphi and 92% in S.typhi. Similarly sensitivity of Azithromycin was 92% and 93% for S.typhi and S. paratyphi respectively. Conclusion: Salmonella serotype is still 100 % sensitive to third generation cephalosporin. Some percentage of resistance is seen with Ofloxacin in S. typhi and with Azithromycin in both S.typhi and S. paratyphi. Key words: Enteric fever; S.typhi; S.paratyphi; Sensitivity DOI: http://dx.doi.org/10.3126/jnps.v31i3.4382 J Nep Paedtr Soc 2011;31(3): 180-183